Prognostic impact of recurrences of ventricular tachyarrhythmias and appropriate ICD therapies in a high-risk ICD population - Schupp, Tobias; Akın, Ibrahim; Reiser, Linda; Kern-Bollow, Armin; Taton, Gabriel; Reichelt, Thomas; Ellguth, Dominik; Engelke, Niko; Ansari, Uzair; Mashayekhi, Kambis; Weiß, Christel; Nienaber, Christoph; et al. (Clinical research in cardiology, 2019)
Purpose: The study sought to evaluate the prognostic impact of recurrences of ventricular tachyarrhythmias in consecutive ICD recipients with ventricular tachyarrhythmias on admission. Methods: All consecutive patients surviving at least one episode of ventricular tachyarrhythmias from 2002 to 2016 and discharged with an ICD (pre-existing ICD or ICD implantation at index hospitalization) were included. The primary end-point was all-cause mortality according to the presence or absence of recurrences of ventricular tachyarrhythmias at 5 years. Secondary endpoints comprised the impact of different types of recurrences, appropriate ICD therapies, as well as predictors of recurrences and appropriate ICD therapies. Kaplan–Meier, multivariable Cox regression and propensity score matching analyses were applied. Results: A total of 592 consecutive ICD recipients was included (44% with recurrences of ventricular tachyarrhythmias and 56% without). Recurrences of ventricular tachyarrhythmias were associated with increased all-cause mortality at 5 years (HR = 1.498; 95% CI = 1.052–2.132; p = 0.025). Worst survival was observed in patients with sustained VT or VF as first recurrences compared to non-sustained VT, as well as in patients with cumulative recurrences of non-sustained or sustained VT plus VF, whereas mortality was not affected by the number of recurrences of ventricular tachyarrhythmias (> 4 vs. ≤ 4). Moreover, appropriate ICD therapies were associated with increased all-cause mortality (HR = 1.874; 95% CI = 1.318–2.666; p = 0.001), mainly attributed to secondary preventive ICDs. Finally, atrial fibrillation, LVEF < 35% and non-ischemic car-diomyopathy were identified as predictors of recurrences of ventricular tachyarrhythmias and appropriate ICD therapies. Conclusions: Recurrences of ventricular tachyarrhythmias and recurrent appropriate ICD therapies are associated with increased long-term all-cause mortality in consecutive ICD recipients. Non-ischemic cardiomyopathy, AF and LVEF < 35% revealed to be significant predictors of both endpoints.